Crowd enjoying July 4th celebration, Dawson, Yukon Territory, 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows Captain Jack Crawford in the middle of crowd. Caption on image: "Fourth of July celebration N.W.M.P. Square, Dawson. 99" Copied by Larss and Duclos. PH Coll 306.31